2016
DOI: 10.4103/2277-9175.174955
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin induces edema, hyperesthesia and scaling in a depressed patient; a diagnostic challenge

Abstract: Gabapentin is a common drug used as analgesic and anticonvulsant and also is prescribed for insomnia, depression, obsessive – compulsive disorder and panic attack. We report a case of a 48-year-old man who is prescribed gabapentin because of insomnia, headache, and depressed mood. In the first period of using the drug no complication has been seen. However in the next period, side-effects such as hyperesthesia, scaling and severe localized edema has been observed. After several laboratory tests and imaging, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Older age was associated with an increased incidence of peripheral edema (seen in trials for both Neurontin and Gralise [ 28 , 30 ]) and ataxia (seen in trials for Neurontin [ 28 ]); this association was not seen in trials for pregabalin [ 29 ]. Peripheral edema has been observed in several randomized control trials for gabapentin [ 38 ], and case reports suggest that this finding can be observed within days to 2 weeks of initiation [ 39 41 ]. Providers should counsel patients on this possible reaction in advance of gabapentin initiation so that patients are not alarmed if peripheral edema does develop.…”
Section: Safety Profile Of Gabapentin and Pregabalin In Older Adultsmentioning
confidence: 99%
“…Older age was associated with an increased incidence of peripheral edema (seen in trials for both Neurontin and Gralise [ 28 , 30 ]) and ataxia (seen in trials for Neurontin [ 28 ]); this association was not seen in trials for pregabalin [ 29 ]. Peripheral edema has been observed in several randomized control trials for gabapentin [ 38 ], and case reports suggest that this finding can be observed within days to 2 weeks of initiation [ 39 41 ]. Providers should counsel patients on this possible reaction in advance of gabapentin initiation so that patients are not alarmed if peripheral edema does develop.…”
Section: Safety Profile Of Gabapentin and Pregabalin In Older Adultsmentioning
confidence: 99%
“…Gabapentin was discontinued, and his edema improved over the next few days. The final case, reported by Bidaki et al, 11 described a 48-year-old male with depression and insomnia who experienced severe localized edema that resolved upon discontinuation of gabapentin 300 mg at bedtime.…”
Section: Discussionmentioning
confidence: 97%
“…Peripheral edema from gabapentin is not always dose related, however. There are 3 published case reports 6 , 7 , 11 of patients who developed peripheral edema at doses lower than 1800 mg/d. One case published by Kanbay et al 6 described peripheral edema related to gabapentin in a 76-year-old male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other medications commonly used in seizure management (such as benzodiazepines and gabapentin) have been reported to cause new onset peripheral edema. 5,8…”
Section: Discussionmentioning
confidence: 99%